A Study on Factors Affecting Customer Intention to Use the Express Bus - Nguyen, Van Phuong (H. : ĐHQGHN, 2019)
The improvement of transit service quality is an essential need in developing urban and interstate transportation. Local government, as well as bus service companies, should understand the behavioral intention of passengers to meet their expectations and requirements. This paper aims to highlight such behavioral decisions and investigate dominant factors that influence customers’ decision to use the express bus service. The study explores the case of express bus companies in Tay Ninh province, Vietnam. By using the structural equation model approach to analyze the data collected from 295 passengers, who have experience in using the express bus, the results reveal that service quality has a significantly positive relationship with both perceived value and corporate image. Specifically, customer satisfaction and organizational image also positively influence behavioral intention. Meanwhile, service quality indirectly affects behavioral intention through perceived value and corporate image. Based on the findings, we provide some insightful managerial implications and recommendations to managers of bus carriers, and valuable practical suggestions to policymakers in the local government of Tay Ninh province to improve the service quality to encourage more citizens to use the express bus.